PARENTAL BEREAVEMENT: EXPERIENCES OF THE NURSING STAFF IN NEONATAL INTENSIVE CARE - Pires, Luciana de Carvalho; Costenaro, Regina Gema Santini; Gehlen, Maria Helena; Pereira, Liliane Alves; Hausen, Camila Freitas; Neves, Eliane Tatsch (Cogitare Enfermagem, 2023)
Objective: to know the experience of the nursing team when acting in situations of parental bereavement in Neonatal Intensive Care. Method: qualitative study developed through semi-structured interviews from March to April 2021 with nursing professionals from a Neonatal Intensive Care Unit in Rio Grande do Sul, Brazil. The results were submitted to thematic content analysis. Results: The act of experiencing parental bereavement by the nursing staff involves sadness, helplessness, and suffering. Strategies faced at this moment are based on empathy and humanization. For the professionals, the knowledge to face the situation comes from their own experiences of loss in their personal and professional lives, from their strength and religiosity. Conclusion: it is expected that this study contributes to the practice of health professionals in assisting parents who experience the process of parental bereavement in neonatal intensive care.